Моделювання очищення поверхонь потоком абразивних часток - Ясев, О.Г. (Physico-technological Institute of Metals and Alloys, 2023)
Utilization of system of mathematical modeling, which consists of mathematical modeling, creation of constructional and technological propositions and optimization parameters of equipment during the creation of technological equipment for cleaning surfaces by the stream of abrasive particles on the example of cleaning holes with small diameters in details of elements of hydraulic machines is described. Estimation and confirmation of adequacy of mathematical model are executed by means of criterion of verification of accordance for small selections. As a criterion of optimization intensity of output of material is accepted from the elementary ground of surface at total influence of plenty enough of abrasive particles. The optimized technological parameters are sizes of grittiness of abrasive and speeds of particles of stream, providing maximal intensity of output of material. Technical documentation is not envisage the special requirements to the roughness of surface of opening, therefore in the conditions of this task limitation on a roughness assumes a special air of condition of ungrowth of roughness at treatment. Set structurallytechnological parameters, rigging providing the stable receipt of the homogeneous cleared internal surfaces of pistons of axialpiston hydromashines is used in the construction of rigging and technology of its application. In the technological process of making of pistons on the plant-manufacturer of axialpiston hydromachines the operation of cleaning of opening is entered after chemical-thermal treatment with the use of the offered technological equipment. Such approach is universal in relation to the form of surfaces and type of mathematical model, provides the necessary level of exactness and allows effectively solve the practical tasks of creation of the technological equipment for upgrading cleaning of surfaces.